The virgin diet: drop 7 foods, lose 7 pounds, just 7 days ebook - Virgin, JJ (2012)
Your fat is not your fault. Are you eating all the right things--low-fat yogurt, egg-white omelets, whole-grain bread, even tofu--but still can't lose the weight? Your favorite "diet" foods may be to blame. In this groundbreaking program, nutrition and fitness expert JJ Virgin reveals the real secret behind weight gain-- food intolerance. A negative reaction to certain foods like dairy or gluten can sabotage your health by triggering inflammation and causing a host of nasty symptoms like bloating, breakouts, headaches, achy joints and--worst of all--stubborn weight gain. On The Virgin Diet, you'll eat plenty of anti-inflammatory, healing foods to reclaim your health and reset your metabolism, while avoiding the 7 foods that are most likely to cause food intolerance. You'll never feel hungry or deprived, and in just one week, you'll drop up to 7 pounds, lose belly bloat, gain energy, clear up inflammation and look and feel years younger. And that's just the beginning!